Modelling Determinants of Farmers’ Choice of Adaptation Strategies to Climate Variability and Extreme Events in Kitui County, Kenya - Mutunga, Evelyn J.; Ndungu, Charles K.; Mwangi, Moses; Kariuki, Patrick C. (International Journal of Environment, Agriculture and Biotechnology, 2020)
The study was carried out to assess determinants of farmers’ choice of specific adaptation strategies to climate variability and extreme events in selected agro-ecological zones in Kitui County. Descriptive survey design was used. The study area was stratified into four study sites with respect to four different agro-ecological zones and a total of 341 households selected to constitute the sample size. Multivariate probit regression model was run in Stata version 12 to determine the influence of different socio-economic characteristics on farmers’ choice of specific adaptation strategies. The model results indicated that age, gender, farming experience, membership to farmers’ organization, education level, access to extension services and proximity to market had a significant varying influence on farmers’ choice of several adaptation strategies. The study established that different socio-economic characteristics had a different influence on the farmers’ choice of specific adaptation strategies. The study therefore recommends that climate variability adaptation policies, programs and projects by governmental and non-governmental development agencies should target specific socio-economic characteristics that are relevant to the adaptation strategies in question.